Mindfulness, Self-Compassion, dan Humor Styles - Ka Yan; Priska Analya; Lie Fun Fun (Jurnal Ilmu Perilaku, 2021)
Variables of this study are mindfulness, self-compassion, and humor styles that are related to mental health, which are important and become the attention in the world. The purpose of this study was to determine the role of mindfulness and self-compassion in a single way or combine with humor styles. Sample consisted of 261 students from 447 populations and used quantitative approach. Results of the first phase using linear regression to see role of mindfulness toward humor styles stated that mindfulness did not play a role in affiliative humor, but there was a negative role between mindfulness on self-enhancing, aggressive, and self-defeating humor. The second phase using multiple linear regression to see role of mindfulness and self- compassion simultaneously with humor styles show there was a role for mindfulness and self- compassion towards affiliative and self-enhancing, in which self-compassion played a greater role. Whereas in aggressive and self-defeating, self-compassion had less role. Based on a review of the four humor styles, mindfulness and self-compassion have the most role in self-enhancing humor. Thus, researchers suggest students to improve their mindfulness and self-compassion by adding insight, training, and applying them in everyday life.